The Effect of Experiential Marketing and Product on Repurchase Intention at Azuraya Vapor Ampera Mediated by Customer Satisfaction in Pontianak - Siti Muna Azizah; Helman Fachri (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of experiential marketing and product on repurchase intention, both directly and indirectly through customer satisfaction as a mediating variable at Azuraya Vapor Store Ampera in Pontianak City. The study uses a quantitative approach with a causal associative research type. Data were collected through a Likert-scale questionnaire distributed to 100 respondents selected using purposive sampling, with criteria of consumers aged at least 21 years and having made purchases at least twice. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS software. The results show that experiential marketing and product have a positive and significant effect on customer satisfaction. Customer satisfaction is also proven to have a positive effect on repurchase intention. However, experiential marketing does not have a direct effect on repurchase intention, but rather has an indirect effect through customer satisfaction. Meanwhile, product affects repurchase intention both directly and indirectly through customer satisfaction. These findings confirm that customer satisfaction is a key factor in converting experience and product quality into repurchase intention in vape retail.